Fuzzy sliding mode power control for wind power generation systems connected to the grid - Imane El Kararoui; Mohamed Maaroufi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In recent years we have witnessed a real increase in the production of wind turbines and wind farm installations around the world, in order to improve this own energy, several studies have focused on the interest of controlling the active and reactive power of the system. Wind power, and at the same time on the quality of the energy produced and its connection in order to ingest suitable electrical energy into the distribution network. This article studies a new control technology to meet the various constraints in the field. The objective for work is to develop and study the sliding mode control method applied to a wind power system based on doubly fed induction generation (DFIG), as well as an optimization using the fuzzy logic technique. Ensuring the stability of the system is one of the objectives of using the Lyapunov nonlinear technique in the sliding mode control strategy which will be applied to the two converters (machine side and network side). The proposed solution was to validate a simulation on MATLAB/Simulink, tracking test (true wind speed) and also the robustness of the system.